Estudio seguimiento: programa Escuela centro de cambio Nivel secundario (período 2003 2007) - Calneggia, María Isabel; Larrovere, Cecilia; Coschica, Jorge; Di Francesco, Adriana; Furlán, Silvia; Lázaro, Lucas; Monteverdi, Griselda (Anuario Digital de Investigación Educativa, 2019)
Ninguno